Fungal β‐Mannosyloxymannitol Glycolipids and Their Analogues: Synthesis and Mincle‐Mediated Signaling Activity. Issue 20 (20th May 2022) - Matsumaru, Takanori; Sakuratani, Kasumi; Yanaka, Saeko; Kato, Koichi; Yamasaki, Sho; Fujimoto, Yukari
Abstract: Mincle, a C‐type lectin receptor (CLR), senses certain lipid conjugates, leading to the activation of the innate immune system. The lipid conjugate ligands include glyco‐, glycero‐, and mannitol lipids. Recently, a fungal β‐mannosyloxymannitol glycolipid demonstrating a novel architecture, "44‐2, " was isolated from the fungus Malassezia and displayed potent Mincle‐mediated signaling activity. For this study, we synthesized the diastereomeric pair of mannosyloxymannitol glycolipids and their analogues and analyzed the structure‐activity relationships of Mincle‐mediated signaling. The results suggest that the dimannosyl‐fatty acid moiety in the mannosyloxymannitol glycolipid‐type structure plays a major role in the molecular recognition of Mincle. Abstract : The diastereomeric pair of mannosyloxymannitol glycolipids and its analogues were synthesized and analyzed for the structure–Mincle‐mediated signaling activity relationships. The results suggest that the dimannosyloxy fatty acid moiety of the mannosyloxymannitol glycolipid plays a major role in the molecular recognition of Mincle.